Respiratory and C4-photosynthetic NAD-malic enzyme coexist in bundle sheath cell mitochondria and evolved via association of differentially adapted subunits. Issue 1 (4th November 2021) - Hüdig, Meike; Tronconi, Marcos A; Zubimendi, Juan P; Sage, Tammy L; Poschmann, Gereon; Bickel, David; Gohlke, Holger; Maurino, Veronica G
Abstract: In plant mitochondria, nicotinamide adenine dinucleotide-malic enzyme (NAD-ME) has a housekeeping function in malate respiration. In different plant lineages, NAD-ME was independently co-opted in C4 photosynthesis. In the C4 Cleome species, Gynandropsis gynandra and Cleome angustifolia, all NAD-ME genes ( NAD-MEα, NAD-MEβ1, and NAD-MEβ2 ) were affected by C4 evolution and are expressed at higher levels than their orthologs in the C3 species Tarenaya hassleriana . In T. hassleriana, the NAD-ME housekeeping function is performed by two heteromers, NAD-MEα/β1 and NAD-MEα/β2, with similar biochemical properties. In both C4 species, this role is restricted to NAD-MEα/β2. In the C4 species, NAD-MEα/β1 is exclusively present in the leaves, where it accounts for most of the enzymatic activity. Gynandropsis gynandra NAD-MEα/β1 (GgNAD-MEα/β1) exhibits high catalytic efficiency and is differentially activated by the C4 intermediate aspartate, confirming its role as the C4 -decarboxylase. During C4 evolution, NAD-MEβ1 lost its catalytic activity; its contribution to the enzymatic activity results from a stabilizing effect on the associated α-subunit and the acquisition of regulatory properties. We conclude that in bundle sheath cell mitochondria of C4 species, the functions of NAD-ME as C4 photosynthetic decarboxylase and as a housekeeping enzyme coexist and are performed by isoforms that combine the same α-subunit with differentially adapted β-subunits. Abstract : In C4 bundle sheath cell mitochondria, the housekeeping and C4 -decarboxylase functions of NAD-ME are performed by isoforms that combine the same α subunit with differentially adapted β subunits.